(untitled) (Archives of Mechanics - Test, 2013)
If a shape memory alloy (SMA) is subjected to the subloop loading under the stress-controlled condition, creep and creep recovery can appear based on the martensitic transformation. In the design of SMA elements, these deformation properties are important since the deflection of SMA elements can change under constant load. The conditions for the progress of the martensitic transformation are discussed based on the kinetics of the martensitic transformation for the SMA. The creep deformation properties are investigated experimentally for TiNi SMA. The creep strain rate increases in proportion to the martensitic transformation strain; the creep recovery strain rate increases in proportion to the reverse transformation strain.